Perceived HR Practices and Intention to Quit of Generation X and Y in Unionize Organization - Kadiresan, Vimala; Kumar Moona Haji Mohamed, Ramesh; Ramendran SPR, Charles; Nadarajah, Shanti; Kakar, Samad (International Journal of Engineering and Technology, 2018)
Hotel industry is one of the important segments that contribute greatly to the worldâ€™s economy. The intention of employees to quit is very crucial in any organization especially in the service industry. The importance of this study is to provide some insights on how organizations, (specifically hotel industry) could apply various management styles to different generations in the workplace. Nearly 269Â usable survey questionnairesÂ haveÂ been collected from 25 unionize hotel employees in Peninsular of Malaysia and the data hasÂ been analyzed with partial least squares (PLS) 2.0.The studies revealÂ that factors like performance appraisal and remuneration are not important factors for Gen Y employees to leave the organization. Moreover R square shows 58.6 %, which negatively relates to anÂ Â intention to quit, explainingÂ Â total variance. The findings show that, Gen Y have a set of characteristics that is different from other employees and they are always on a look outÂ Â to innovate and highlight their talents. Furthermore, the findings of this study provide some practical implications on the effect of the intention to quit in the hotel industry. It also could help the managers and Human Resource department to have better understanding in managing and coping with the turnover issues in the hotel industry.Â